Peningkatan Efisiensi Operasional Perkantoran melalui Integrasi Microsoft Office dan Artificial Intelligence di Perumda Air Minum Tirta Mangutama Kabupaten Badung - I Putu Gd Sukenada Andisana; Pande Putu Ode Juliantara KW; Anak Agung Gde Wahyu Sukma Erlangga; Ni Nyoman Emang Smrti; Ibnu Atho'illah; Desak Made Pratiwi Dharayanti; I Wayan Sutarjana; Acep Taufik Hidayat; Ni Kadek Juliarini; Ni Made Ari Lestarini; Ida Ayu Surya Maharani (Universitas Pahlawan Tuanku Tambusai, 2026)
The low level of office software optimization and employees’ limited digital literacy are major obstacles to operational efficiency in the public service sector, including at Perumda Air Minum Tirta Mangutama. This Community Service activity aims to enhance employees’ technical competencies through Smart Office Productivity training that integrates advanced Microsoft Office features with Artificial Intelligence (AI) technology. The method used is participatory training based on demonstrations and hands-on practice, with evaluation conducted through a comparison of pre-test and post-test scores as well as the calculation of Normalized Gain (N-Gain). The results of the activity showed an increase in the average participant score from 66.25 to 76.25, with an average N-Gain of 0.29. This training has proven capable of driving the transformation of employee competencies toward a productive and efficient smart work ecosystem in support of improving the quality of public services.